Image transmission over cognitive radio systems with channel and sensing uncertainty - Chuang Ye; Ozcan, Gozde; Gursoy, M. Cenk; Velipasalar, Senem (2015 IEEE Global Conference on Signal and Information Processing (GlobalSIP), 2015)
This paper studies the performance of hierarchical modulation-based image transmission over cognitive radio systems operating with imperfect channel sensing results and also imperfect channel state information (CSI) regarding the interference link between the secondary transmitter and primary receiver. First, closed-form bit error rate (BER) expressions for high priority (HP) data and low priority (LP) data are derived. Subsequently, the optimal power control policies which minimize the weighted sum of upper bounds on average BERs of HP bits and LP bits subject to peak/average transmit power and average interference power constraints are determined under the assumption of imperfect CSI of the interference link. The effects of power levels of pilot signals used for channel estimation and the impact of imperfect channel sensing decisions on the performance of cognitive transmissions are analyzed in terms of the received image quality and number of retransmissions.